Study of incidence of occult pneumomediastinum due to blunt chest trauma (Asian Journal of Medical Sciences, 2024)
Background: Pneumomediastinum refers to the presence of extraluminal gas within the mediastinum. If signs of pneumomediastinum are not present on chest X-ray and it is detected on contrast-enhanced computed tomography (CECT) thorax then it is known as occult pneumomediastinum. There is a dearth of literature regarding occult pneumomediastinum in patients with blunt chest trauma.Aims and Objectives: This study was done to see the incidence as well as outcome of occult pneumomediastinum in patients of blunt chest trauma.Materials and Methods: A prospective study was done in the department of general surgery at a tertiary care institute in which a total of 32 patients with blunt chest trauma were taken. The patients with occult pneumomediastinum were identified using CECT and appropriate management was done in all patients. Correlation of occult pneumomediastinum with subcutaneous emphysema, rib fracture, jugular venous pressure (JVP), pleural effusion, and outcome was seen.Results: It was evident from this study that 18.8% of patients of with chest trauma had occult pneumomediastinum. Incidence of blunt chest trauma is most common in the age group of 31–60 years as this age group is more vulnerable to roadside accidents and other accidents. There is a strong correlation between the presence of central subcutaneous emphysema, raised JVP, and worse outcomes with occult pneumomediastinum (P